Oral communication skills of level III children with mild mental retardation in selected public schools: An assessment - Ho, Chin-Gwang (Hamen) (Animo Repository, 2002)
This is an assessment study on the Oral Communication Skills of Level III Children with Mild Mental Retardation in terms of listening and speaking skills through teacher-made tests. Specifically, it looks into the oral communication skills of the sampled children with mild mental retardation in selected public schools with SPED centers at Bo. Obrero Elementary School, Legarda Elementary School, M. Hizon Elementary School, P. Burgos Elementary School, P. Gomez Elementary School and Rizal Elementary School in terms of listening and speaking skills their strengths and weaknesses in both areas, and the correlation of their listening with their speaking skills.The study employed the descriptive method of research utilizing a teacher-made test based on the competencies of level III children with mild mental retardation and developed by the Special Education Unit of the Department of Education. Findings of the study revealed that more than 50 percent of the respondents possessed listening skills and speaking skills expected of them. Majority have mastered identifying sounds in the environment, following directions and answering yes-no questions, speaking skills relative to talking about themselves and the members of their families. However, majority of the respondents had difficulty in discriminating similar and dissimilar words, identifying and producing words that rhyme, and answering wh-questions. Results of the study revealed that the listening skills of level III children with mild mental retardation have positive and significant correlation with their speaking skills.